Pengaruh Laverage Maturity dan Size Perusahaan Terhadap Yield Obligasi Dengan Peringkat Obligasi Sebagai Variabel Intervening - Faizah, Yuniar Laeli Nur (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2019)
This study aims to get empirical evidence on the effect of leverage, maturity, and size of the company against the results with intervening variables. The population in this study is all companies listed in Indonesia Stock Exchange (BEI) during 2011-2015 which has bonds inperiod 2012-2016.These bonds were assessed by rating agents of PT. Pefindo. Testing is done by using the path analysis, to determine the effect of leverage, maturity, and size of the company to the bond rating. Second path is for leverage, maturity, size, and ranking of results. Sobel test to process the mediation / intervening. The results show that leverage does not affect the rank, maturity and size of the company signed to the rating of bonds. The results of the road trials show that leverage and size have no effect on yield, maturity and assessment have a significant effect on results. From the Sobel, Results to test the test capable of mediating leverage variables, and the size of the bond yield, while the maturity of the results cannot be mediated by the bond rating.